The outcome of cataract surgery in eyes with end-stage glaucoma - Gračner, Tomaž (Acta medico-biotechnica, 2013)
Purpose: To evaluate the outcome of phacoemulsification and intraocular lens implantation (PHACO IOL) in eyes with endstage glaucoma. Methods: Eighteen eyes of 18 patients with endstage glaucoma in which PHACO IOL was performed were included in this prospective clinical study. Intraocular pressure (IOP) was measured before and 1 week, and 1, 3, 6, and 12 months after PHACO IOL. The best corrected visual acuity (BCVA), the number of antiglaucoma medications and the visual field (VF) test results before PHACO IOL and at the end of followup were evaluated. Results: The followup period after PHACO IOL was 12 months for all eyes. The mean IOP before surgery was 13.5 mmHg (SD 2.6). There were no differences between the mean IOP measurements before and after surgery during the entire followup period (P>0.05). The mean preoperative BCVA was 0.65 (SD 0.3) logMAR, improving to a mean of 0.19 (SD 0.1) logMAR postoperatively (P<0.0001). The mean number of antiglaucoma medications before surgery was 1.8 (SD 1.4), and it was 2.0 (SD 1.3) postoperatively (P=0.104). The mean value of the mean deviation in 7 eyes on automated perimetry was 23.57 dB (SD 3.9) preoperatively and 22.87 dB (SD 4.1) postoperatively (P=0.105). The mean VF island in 11 eyes on Goldmann perimetry was 17.0° (SD 7.2) preoperatively, improving to 20.4° (SD 9.0) postoperatively (P=0.033). Conclusion: PHACO IOL in eyes with endstage glaucoma resulted in a stable IOP and a significantly improved BCVA without worsening of the VF.
Keywords: glavkom; izid zdravljenja; oftalmološki kirurški postopki; siva mrena; zadnji stadij